De patricios y nación - María Cruz Romeo Mateo (Mélanges de la Casa de Velázquez, 2005)
This article seeks to analyse the culture of «modern politics» on the basis of the value system displayed by Spanish liberal politicians in the mid-19th century. Centring on the private correspondence of the progressive Fermín Caballero, the author examines the way in which the patriciate and the local and national community were projected in the jockeying typical of electoral periods. She looks closely at the problem of the kind of liberal politics that rejected and questioned the legitimacy of inter-party struggles, the plurality of the citizenry and the diversity of civil society. Finally, the article proposes a comparative perspective through which to address both the historical specificities of European liberalism and the contributions of other disciplines besides history.